Analisis Kemampuan Literasi Sains Siswa SMP Umar Masud - Yuni Sri Rahayu; Erman Erman; Karimah Karimah; Aunur Rofiq; Muhammad Azimul Anshar (Postgraduate, University of Mataram, 2023)
Scientific literacy is the main key in facing the challenges of the 21st century. The reason for the low ability of students in scientific literacy is the lack of scientific literacy content in teaching materials. The importance of students' knowledge of scientific literacy skill information is to provide solutions to problems in the field of literacy. This study aimed to determine the scientific literacy abilities of Class VII students of the Umar Mas'ud Sangkapura School. A combination descriptive research method was used in this study. Under the direction of the Umar Mas'ud School, a cluster random sampling method was used to select the research sample, which included 40 seventh graders from MTS Umar Mas'ud and SMP Umar Mas'ud. The instrument was carried out by testing scientific literacy questions and interview guideline sheets. The results of the scientific literacy tests and interviews were carried out using data analysis techniques by giving a score to each student's answer. The data obtained were interpreted into two categories, scientific literacy scores, and interview results. The average grade VII grade IPA students of the Umar Mas'ud Sangkapura Foundation are 32,563, placing them in the low category. There are several factors that cause students' low scientific literacy skills, including a lack of interest in reading, instructional media that do not prioritize scientific literacy, and a lack of direction from the teacher